2000
DOI: 10.1002/(sici)1097-0290(20000205)67:3<327::aid-bit9>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between cellobiose catabolism, enzyme levels, and metabolic intermediates inClostridium cellulolyticum grown in a synthetic medium

Abstract: Continuous cultures, under cellobiose sufficient concentrations (14.62 mM) using a chemically defined medium, were examined to determine the carbon regulation selected by Clostridium cellulolyticum. Using a synthetic medium, a qcellobiose of 2.57 mmol g cells−1 h−1 was attained whereas the highest value obtained on complex media was 0.68 mmol g cells−1 h−1 (Payot et al. 1998. Microbiology 144:375–384). On a synthetic medium at D = 0.035 h−1 under cellobiose excess, lactate and ethanol biosynthesis were able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
3
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 39 publications
4
65
3
1
Order By: Relevance
“…This is similar to the rate of cellulose degradation observed for C. thermocellum at 60°C (33,36). However, no further cellulose degradation or cell growth was observed after 60 h. This could be due to either the depletion of a particular nutrient from the culture medium (21) or an accumulation of inhibitory intracellular compounds in the medium or in the cell (10,20). Various types of cellulase enzymes could be inhibited by soluble products (glucose, cellobiose, cellotriose, etc.)…”
Section: Resultscontrasting
confidence: 56%
“…This is similar to the rate of cellulose degradation observed for C. thermocellum at 60°C (33,36). However, no further cellulose degradation or cell growth was observed after 60 h. This could be due to either the depletion of a particular nutrient from the culture medium (21) or an accumulation of inhibitory intracellular compounds in the medium or in the cell (10,20). Various types of cellulase enzymes could be inhibited by soluble products (glucose, cellobiose, cellotriose, etc.)…”
Section: Resultscontrasting
confidence: 56%
“…During growth of C. cellulolyticum in complex medium, NADH/NAD ϩ ratios as high as 57 have been reported, suggesting that catabolism is limited by the rate of NADH reoxidation (226,519). Inability to regenerate NAD ϩ leads to metabolism of excess carbon via phosphoglucomutase, with the G-1-P ultimately used for cellodextrin synthesis and efflux, intracellular glycogen synthesis, and extracellular polysaccharide production (225,227). The difficulty in reoxidizing NADH may explain why this species is the only mesophilic cellulolytic organism reported to produce lactate in excess of 0.5 mol per mol of hexose consumed (156).…”
Section: Physiology Of Cellulolytic Microorganismsmentioning
confidence: 95%
“…This excess of produced NADH correlated with increases of both the H 2 / CO 2 ratio, which was always higher than 1, and the q NADH-Fd . These results suggested that the intracellular NADH/NAD ϩ ratio was maintained by the NADH-Fd reductase and hydrogenase, since these interconnected enzymatic activities can oxidize NADH via H 2 production (18)(19)(20). The O/R, determined from the gas production ratio and fermentative end product concentration, was very close to 1 and indicated an efficient reoxidation of NADH via H 2 production in addition to carbon fermentative pathways (11).…”
Section: Cellulolyticum Catabolism At High Cellulose Levels 3841mentioning
confidence: 99%
“…Using cellobiose, which is one of the soluble cellodextrins released during cellulolysis, major differences in the regulation of the carbon flow between carbon-limited and carbon-sufficient continuous cultures have been reported (19,20). As the dilution rate increases, in cellobiose-limited chemostats the metabolic pathways towards ethanol and lactate contribute to balance the reducing equivalents supplied by acetate formation (19), while under cellobiose-saturated conditions (20) the redox balance is essentially maintained by NADH-ferredoxin (NADH-Fd) reductase-hydrogenase and ethanol dehydrogenase activities and the carbon flow is equilibrated by three overflows, i.e., exopolysaccharide, extracellular protein, and amino acid excretions.…”
mentioning
confidence: 99%
See 1 more Smart Citation